Associations in asthma between quantitative computed tomography and bronchial biopsy-derived airway remodelling. Issue 5 (2nd May 2017) - Berair, Rachid; Hartley, Ruth; Mistry, Vijay; Sheshadri, Ajay; Gupta, Sumit; Singapuri, Amisha; Gonem, Sherif; Marshall, Richard P.; Sousa, Ana R.; Shikotra, Aarti; Kay, Richard; Wardlaw, Andrew; et al.
Airway remodelling in asthma remains poorly understood. This study aimed to determine the association of airway remodelling measured on bronchial biopsies with 1) lung function impairment and 2) thoracic quantitative computed tomography (QCT)-derived morphometry and densitometry measures of proximal airway remodelling and air trapping. Subjects were recruited from a single centre. Bronchial biopsy remodelling features that were the strongest predictors of lung function impairment and QCT-derived proximal airway morphometry and air trapping markers were determined by stepwise multiple regression. The best predictor of air trapping was validated in an independent replication group. Airway smooth muscle % was the only predictor of post-bronchodilator forced expiratory volume in 1 s (FEV1 ) % pred, while both airway smooth muscle % and vascularity were predictors of FEV1 /forced vital capacity. Epithelial thickness and airway smooth muscle % were predictors of mean segmental bronchial luminal area (R 2 =0.12; p=0.02 and R 2 =0.12; p=0.015), whereas epithelial thickness was the only predictor of wall area % (R 2 =0.13; p=0.018). Vascularity was the only significant predictor of air trapping (R 2 =0.24; p=0.001), which was validated in the replication group (R 2 =0.19; p=0.031). In asthma, airway smooth muscle content and vascularity were both associated with airflow obstruction. QCT-derived proximal airway morphometry was most strongly associated with epithelial thickness and airway smooth muscle content, whereas air trapping was related to vascularity. Airway remodelling in asthma biopsies is associated with proximal airway QCT-derived morphometry and air trapping http://ow.ly/ucoA308Jv9F